Construção e validação de um instrumento de classificação de risco e condutas adequadas para pacientes com hipertensão arterial sistêmica - Silva, Gilvan Gomes da (2021)
Systemic arterial hypertension when not properly treated can be the first step that leads to institutionalization and loss of functional independence, since when hospitalization occurs, many patients experience a period of reduced mobility and functional activities, generating impairment your physical state and vitality. The use of instruments that allow data collection according to the characteristics and specificities of the individuals to be assisted, in order to assist in the professional's decision process, constitutes a methodological resource that collaborates in improving the quality of care, evaluating responses to treatments, it provides the comparison of data over time, in addition to guiding clinical practice. Objective to build and validate an instrument for risk classification and appropriate conduct regarding the content for patients with systemic arterial hypertension for use in primary health care. Methodological study, consisting of three stages: elaboration of an integrative review, discussion and braistorming and validation of the instrument. Sample was for convenience and composed of experts according to the inclusion criteria. An instrument in the form of a Likert-type questionnaire was developed. The construction took place through an integrative review, and constructive brainstorming discussions. The validation was performed using the Delphi technique. The data were stored in the Google Forms database and exported for analysis with software R. Quantitative analysis by calculating the content validity index (CVI) The content validity of the items in this study was considered when CVI ≥ 0, 80, according to the methodological framework, in addition to the binomial and Kappa tests. At the end of the round, the 46 items were validated, none reached the exclusion consensus and the result of the Kappa test showed an almost perfect agreement, with a value of 0.90 for all items. With this study, it was possible to build and validate an instrument regarding its content through the Delphi method composed of 46 items, which can be used to classify risk and appropriate behaviors for hypertensive patients in Primary Health Care.